Performance study of sodium alginate-nonwoven fabric composite membranes for dehumidification. (5th January 2018) - Xu, Jingcui; Zhang, Chuanyu; Ge, Tianshu; Dai, Yanjun; Wang, Ruzhu
Highlights: The composite membrane SA-NWFs for dehumidification is fabricated in a simple way. Water vapor permeance of membranes increases with the increasing LiCl mass. Working efficiencies of the ERV with composite membranes are higher. The composite membranes show great potential to be applied on the ERV. Abstract: A novel composite membrane is proposed to improve the dehumidification performance of the membrane-based energy recovery ventilator (ERV). In this study, the composite materials based on nonwoven fabrics, sodium alginate and lithium chloride (LiCl) were fabricated. Nonwoven fabrics were adopted as supporting constructions; sodium alginate and LiCl were the corresponding active layer and hydrophilic additive. Membranes with different LiCl mass fraction were tested and analyzed to evaluate practical performance when applied in the ERV. Results show that the highest vapor permeance of the composite membrane is 29.8 × 10 −8  kg/m 2 ·s·Pa, 10 times higher than that of composite one without LiCl. Water solubility declines to 20.6%, which demonstrates a certain waterproofness of membranes. Besides, simultaneous thermal analysis shows that LiCl accelerates evaporation rate of bound water. Furthermore, two ERVs with different composite membranes are fabricated and characterized by measuring their sensible, latent and enthalpy efficiencies. It is found that these three efficiencies can reach up to 83.9%, 87.4% and 86.7% under summer condition, and 80.8%, 81.7%, and 81.1% under the winter condition, respectively.